ANALISIS PENGARUH PERSEPSI HARGA, KEPERCAYAAN PELANGGAN, KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN (Studi pada Waroeng Steak & Shake Semarang Cabang Kelud) - Chendradewi, Ranny; Khasanah, Imroatul (Diponegoro Journal of Management, 2016)
The rapid development of the culinary business in the city of Semarang is also supported by consumer behavior itself. Family cities tend to be practical, they choose instant food and liked the restaurant with atmosphere "homey". This phenomenon is supported by the habits of Semarang people are likely to visit a restaurant or a place to eat with a variety of purposes in addition to eating a meal, like hanging out with relatives or family, for a business meeting, or celebrate an event, etc.               The population is all existing customers Waroeng Steak and Shake Branch Sampangan. samples taken in the study was obtained for 96.04 and then rounded up to 100 people. The analysis tool used is multiple linear regression were first tested by using validity and reliability.            The results showed that the influences of the positive and significant correlation between perception of price on purchase decisions. This means that if the price is affordable then buying decision will increase. There are significant positive and significant correlation between the quality of products on purchase decisions. This means that any increase in the belief it will increase keptuusan pembelianTerdapat positive influence and significant correlation between customers' confidence in purchasing decisions. This means that any increase in the belief it will increase keptuusan pembelian.Terdapat positive influence and significant correlation between the quality of service to the purchasing decision. This means that any increase in the quality of service will improve purchasing decisions.